Eukaryotické mikroorganismy jako biologické továrny na přípravu nanočástic kovů - Miškovská, Anna; Čejková, Alena (Chemické listy, 2022)
The use of microorganisms as reducing and stabiliz-ing agents in biogenic syntheses of metal nanoparticles is an attractive approach. There is a large number of potential bioagents able to yield big amounts of various biomole-cules, and to prepare nanoparticles of diverse physico-chemical properties. Microscopic fungi and algae are widely studied for the preparation of nanoparticles, mainly because of their ability to produce vast amounts of extra-cellular proteins, enzymes, and other metabolites that can actively participate in the metal reduction and also contrib-ute to the nanoparticle stabilization. This results in highly stable metal nanoparticles with interesting properties that can be used, for example, as antimicrobial agents (especially Ag or Cu nanoparticles) or as catalysts. This review summarizes the main, promising representatives of microscopic fungi, yeasts, and algae used for the prepara-tion of nanoparticles of various metals.
Keywords: nanočástice; Metal Nanoparticles; Fusarium; Eukaryotic Cells; kovové nanočástice; Yeasts; Penicillium; kvasinky; Nanoparticles; Trichoderma; eukaryotické buňky; houby; Fungi; Eukaryota